Impact of sex on outcomes after surgery for non-muscle-invasive and muscle-invasive bladder urothelial carcinoma: a systematic review and meta-analysis - Mori, Keiichiro; Yanagisawa, Takafumi; Katayama, Satoshi; Laukhtina, Ekaterina; Pradere, Benjamin; Mostafaei, Hadi; Quhal, Fahad; Rajwa, Pawel; Moschini, Marco; Soria, Francesco; D'andrea, David; Abufaraj, Mohammad; et al. (World journal of urology, 2023)
PURPOSE: To assess the prognostic value of sex for non-muscle-invasive/muscle-invasive bladder urothelial carcinoma (NMIBC/MIBC) treated with radical surgery. METHODS: The PubMed, Web of Science, and Scopus databases were searched in November 2021 according to the Preferred Reporting Items for Systematic Review and Meta-analysis statement. Studies were deemed eligible if they involved the comparison of the overall, cancer-specific, progression, and recurrence-free survival of patients with NMIBC/MIBC. Formal sex-stratified meta-analyses of these outcomes were performed. RESULTS: Thirty-one studies, which included 32,525 patients with NMIBC, and 63 studies, which included 85,132 patients with MIBC, were eligible for review and meta-analysis. Female sex was associated with worse cancer-specific survival (pooled hazard ratio [HR], 1.21; 95% confidence interval [CI], 1.11-1.31) and overall survival (pooled HR, 1.02; 95% CI, 1.00-1.05) in patients with MIBC. In contrast, however, sex was not associated with cancer-specific survival (pooled HR, 1.01; 95% CI, 0.70-1.46), progression-free survival (pooled HR, 1.04; 95% CI, 0.88-1.24), and recurrence-free survival (pooled HR, 1.06; 95% CI, 0.98-1.16) in patients with NMIBC. CONCLUSIONS: Sex is associated with an increased risk of worse survival outcomes in patients with MIBC but not in those with NMIBC. Given the genetic and social differences between sexes, sex may represent a key factor in the clinical decision-making process.
Keywords: Non-muscle-invasive bladder urothelial carcinoma; Humans; Urinary Bladder Neoplasms; Muscle-invasive bladder urothelial carcinoma; Proportional Hazards Models; ženské pohlaví; karcinom z přechodných buněk; Carcinoma, Transitional Cell; lidé; prognóza; Urinary Bladder; Sex; proporcionální rizikové modely; Female; Prognosis; nádory močového měchýře; Meta-analysis; močový měchýř